TECHNOLOGY CHALLENGES THAT INFLUENCE FAITH, AND CHRISTIAN IDENTITY - Terasa Duha; Andar Gunawan Pasaribu (ASIAN PUBLISHER, 2025)
The digital era has shift values life in a way drastically in the midst of an increasingly modern era proceed this, so that method thinking, interaction man in living spiritually already Far different in the true sense. In context Christianity through development technology can present message Gospel everywhere​ so that people who have not believe and see power Lord in life they capable witness truth Word God in the midst of an increasingly world evil, need to be underlined that, technology is also capable destroy and give long-term negative impacts to faith and identity Christianity moment this. Through study This aim To explore impact technology to faith and formation Christian identity especially digital generation. So that through approach literature in form interview so that study This find the existence of social media as tool in report Gospel to people who have not know Who Jesus Christ and through That lah researchers try not to limited in access information that strengthens values faith in the midst of a globalized era so that Christian identity tends to experience fragmentation when spiritual practices shift from community real to individualistic digital space. Research This emphasizes the importance of spiritual digital literacy and contextual pastoral care so that Christians are able navigate the digital world without losing root faith and identity.